Legal Guarantee of Fisherman Employment Risk through Fisherman Insurance Premium Assistance (BPAN) - Ramlan Ramlan; Faisal Riza (Randwick International of Social Science Journal, 2022)
The number of fishermen who have not received legal protection against safety guarantees has created concerns. So that fishermen need the government's role in getting guarantees in the form of insurance. Insurance programs for fishermen must be continued and developed to ensure the future of fishermen's families. Currently, the government assumes that it has provided insurance policies to all fishermen. Fisherman Insurance Premium Assistance is considered important to ensure protection for their lives and work accidents so that all fishermen and fishermen's families have the confidence to carry out their activities at sea. The provision of insurance through the Insurance Premium Assistance Program for Fishermen (BPAN) is a program to ensure better fisherman activities in the fishing business so that the rights and obligations of fishermen are clear and will be protected in their fishing business activities. As the Law of the Republic of Indonesia Number 07 of 2016 concerning the Protection and Empowerment of Fishermen, Fish Cultivators, and Salt Farmers, has regulated the provision of protection for the work risks experienced by fishermen through the provision of insurance.